Specification of the "coach-teacher" model as a condition for implementing the process of integration of educational, scientific and sports activities in physical education universities - Petrov S.I. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to design a “coach-teacher” model that provides conditions for the implementation of the process of integration of educational, scientific and sports activities of students of physical education universities when mastering basic professional educational programs in the direction of «Sport». Methods and structure of the study. The requirements of professional standards in the field of physical education and sports, which are the basis for the development and implementation of educational programs for the professional training of sports teachers at a physical education university, are analyzed. Comparison of professional competencies formed in accordance with educational standards with the professional functions of a sports teacher at a physical education university, ensuring the process of integration of educational, scientific and sports activities, made it possible to specify the components of the structure of the «coach-teacher» model. Results and conclusions. It has been revealed that the formation of professional competencies of physical education university students in the process of implementing the main professional educational program «Sport», on the one hand, presupposes compliance with a professional standard, and, on the other hand, necessitates the integration of educational, scientific and sports activities of a teacher of higher professional education. The substantive basis of the multifunctional activity of a sports teacher at a physical education university is revealed by the «coach-teacher» model, which is a condition for the implementation of integration processes in the professional training of students at physical education universities and determines prospects, forecasts and innovative ways for the further development of areas of sports training.